Oral health as a risk factor for mortality in middle-aged men: the role of socioeconomic position and health behaviours. Issue 5 (25th September 2012) - Sabbah, Wael; Mortensen, Laust Hvas; Sheiham, Aubrey; Batty, David
Abstract : Background: There is evidence of an association between poor oral health and mortality. This association is usually attributed to inflammatory and nutrition pathways. However, the role of health behaviours and socioeconomic position has not been adequately examined. The aims of this study were to examine the association between oral health and premature death among middle-aged men and to test whether it was explained by socioeconomic position and behaviours. Methods: Data were from the Vietnam Experience Study, a prospective cohort study of Vietnam War-era (1965–1971), American male army personnel. The authors examined risk of cause-specific and all-cause mortality in relation to poor oral health in middle age, adjusting for age, ethnicity, socioeconomic position, IQ, behavioural factors and systemic conditions. Results: Men with poor oral health experienced a higher risk of cause-specific and all-cause mortality. HRs for all-cause mortality were 2.94 (95% CI 2.11 to 4.08) among individuals with poor oral health and 3.98 (95% CI 2.43 to 6.49) among edentates compared with those with good oral health after adjusting for ethnicity and age. The association attenuated but remained significant after further adjustment for systemic conditions, socioeconomic position and behaviours. Socioeconomic and behavioural factors explained 52% and 44% of mortality risks attributed to poor oral health and being edentate, respectively. Conclusion: The findings suggest that oral health–mortality relation is partly due to measured covariates in the present study. Oral health appears to be a marker of socioeconomic and behavioural risk factors related to all-cause mortality.